Morphological Structures of A. Heterophyllus, A. Altilis and A. Camansi - Ebele Josephine Ikwuanusi; Alexander Ikechukwu Izundu (Sean Institute, 2026)
The tropical tree species Artocarpus heterophyllus (jackfruit), Artocarpus altilis (breadfruit), and Artocarpus camansi (breadnut) are highly valuable for global food security, yet their close genetic relationships often lead to taxonomic ambiguities and misidentification. This study evaluated the comparative macromorphological and micromorphological configurations of these three species to establish clear diagnostic boundaries. Plant materials were collected from Aguluezechukwu, Anambra State, Nigeria, and formally authenticated at the Nnamdi Azikiwe University herbarium. Qualitative and quantitative leaf architecture was evaluated using standard botanical frameworks across twenty leaves per species. Qualitative macromorphological assessments revealed that A. heterophyllus possesses simple, elliptical leaves with entire margins and cauliflorous fruiting, whereas A. altilis and A. camansi exhibit terminal fruiting and deeply pinnately lobed laminas. Quantitative morphometric analysis confirmed that A. camansi yields the highest leaf blade length (70.42 +/- 1.48 cm), width (41.50 +/- 0.55 cm), and petiole length (5.68 +/- 0.49 cm), while A. altilis exhibits the highest lateral vein density (27.60 +/- 0.14). Anatomically, A. altilis produces seedless syncarps, contrasting with the many-seeded fruits of A. camansi and A. heterophyllus. In conclusion, explicit vegetative and reproductive structural variations provide definitive taxonomic markers for these taxa. These findings provide essential baseline data for accurate germplasm authentication, biodiversity conservation, and agricultural selection programs.